Optimasi BICS-CALP dalam Kelas Bahasa Arab Inklusif (Al-Hasani: Journal of Islamic Studies, 2025)
Language learning in an inclusive context demands strategies that can accommodate the diversity of student abilities, especially in Arabic language acquisition. One relevant approach is the optimization of Basic InterpersonalCommunicative Skills (BICS) and Cognitive Academic Language Proficiency(CALP). BICS refers to basic communication skills used in everyday interactions, while CALP relates to more complex academic language abilities. In an inclusive environment, optimizing these two aspects becomes a challenge due to differences in language processing speed among students, including those with special needs such as slow learners, ADHD, or communication disorders. This study aims to analyze the optimal strategies in developing BICS and CALP for students in an inclusive Arabic classroom. The research method is based on literature review and classroom observation in an inclusive school, highlighting scaffolding-based approaches, educational technology, and communicative learning models. The results show that a combination of social interaction-based activities to enhance BICS and problem-solving-based approaches to develop CALP can provide more effective results in Arabic language acquisition for inclusive students. In addition, the integration of visual and kinesthetic media was shown to support the linguistic understanding of students with special needs. The implications of this study emphasize the importance of differentiating language learning strategies, as well as adaptation of materials that consider students' cognitive and socio-emotional aspects. Optimizing BICS-CALP in an inclusive classroom not only improves linguistic competence, but also encourages active participation and inclusiveness in Arabic language learning.